2011
DOI: 10.7863/jum.2011.30.11.1509
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Sonographically Guided and Palpation Guided Scaphotrapeziotrapezoid Joint Injections

Abstract: Sonographic guidance can be used to inject the STT joint with a high degree of accuracy and is more accurate than palpation guidance within the limits of this study design. Clinicians should consider using sonographic guidance to perform STT joint injections when precise intra-articular placement is desired. Further clinical investigation examining the role of sonographically guided STT joint injections in the treatment of patients with radial wrist pain syndromes is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 28 publications
0
25
0
1
Order By: Relevance
“…Previous studies have demonstrated that ultrasound guidance may improve efficacy compared with nonguided injections when utilized in various body regions, presumably because of greater accuracy [15,[18][19][20][21][24][25][26][27]. Although no prior study has examined the accuracy or efficacy of SG SM bursa injections, Weiser [13] noted that only 58% of patients with clinically diagnosed SM tendinopathy/bursopathy responded to a single palpationguided injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that ultrasound guidance may improve efficacy compared with nonguided injections when utilized in various body regions, presumably because of greater accuracy [15,[18][19][20][21][24][25][26][27]. Although no prior study has examined the accuracy or efficacy of SG SM bursa injections, Weiser [13] noted that only 58% of patients with clinically diagnosed SM tendinopathy/bursopathy responded to a single palpationguided injection.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, clinicians may consider utilizing precisely placed diagnostic injections to identify the pain generator(s) and facilitate appropriate management in patients presenting with medial knee pain syndromes [15,16]. Furthermore, image-guided therapeutic injections may produce a more predictable benefit than palpationguided injections [13,[15][16][17][18][19][20][21][22][23][24][25][26][27][28]. The role of sonographically guided (SG) diagnostic and interventional procedures in musculoskeletal and sports medicine is well established [15,[18][19][20][21]28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Fakat yine de parasal ve zaman gerektiren bir yöntemdir (2,5). Literatürde ultrasonografinin el bileği enjeksiyonunda etkinliğini gösteren çalışmalar mevcuttur (6)(7)(8)(9)(10)(11). Radyolojik olarak kontrastın eklem içine ve intrensek ligaman rüptürlerine bağlı komşu kompartımanlara geçişini en iyi gösteren yöntem MR artrografidir (3,(4)(5)(6)(7)(8)(9)(10)(11)(12)…”
Section: Methodsunclassified
“…Thus, accurately targeted steroid injections into the STT joint will have the dual diagnostic as well as a therapeutic role. 6 …”
Section: Pathophysiology and Indicationmentioning
confidence: 99%